2004
DOI: 10.1128/jb.186.8.2288-2294.2004
|View full text |Cite
|
Sign up to set email alerts
|

The PmlI-PmlR Quorum-Sensing System in Burkholderia pseudomallei Plays a Key Role in Virulence and Modulates Production of the MprA Protease

Abstract: Burkholderia pseudomallei is the causative agent of melioidosis, an often fatal infection of humans and animals. The virulence of this pathogen is thought to depend on a number of secreted proteins, including the MprA metalloprotease. We observed that MprA is produced upon entry into the stationary phase, when the cell density is high, and this prompted us to study cell density-dependent regulation in B. pseudomallei. A search of the B. pseudomallei genome led to identification of a quorum-sensing system invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 42 publications
4
89
1
1
Order By: Relevance
“…When the concentration of such an excreted metabolite reaches its threshold level, certain types of gene expression resulting in bioluminescence [1], biofilm formation [2,3], swarming motility [4], antibiotic biosynthesis [5,6] virulence factor production [7,8], etc., are triggered by the metabolite (autoinducer). Disruption of the QS system in pathogenic Burkholderia cepacia and B. pseudomallei resulted in reduced pathogenicity in murine and hamster infection [9,10], and erythromycin inhibits biofilm formation of Pseudomonas aeruginosa below the minimum inhibitory concentration (MIC) [11]. Therefore, compounds that inhibit QS have great potential for use in the treatment of bacterial infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…When the concentration of such an excreted metabolite reaches its threshold level, certain types of gene expression resulting in bioluminescence [1], biofilm formation [2,3], swarming motility [4], antibiotic biosynthesis [5,6] virulence factor production [7,8], etc., are triggered by the metabolite (autoinducer). Disruption of the QS system in pathogenic Burkholderia cepacia and B. pseudomallei resulted in reduced pathogenicity in murine and hamster infection [9,10], and erythromycin inhibits biofilm formation of Pseudomonas aeruginosa below the minimum inhibitory concentration (MIC) [11]. Therefore, compounds that inhibit QS have great potential for use in the treatment of bacterial infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In supernatants from B. mallei, the signaling molecules C 8 -HSL and C 10 -HSL were detected ( Table 4). As with B. mallei, it was recently shown that B. pseudomallei 008 produces C 10 -HSL via the PmlI protein (36). Similar to B. mallei, with the exception of N-(3-oxotetradecanoyl)-L-homoserine lactone, B. pseudomallei DD503 synthesizes C 8 -HSL, 3-hydroxy-C 8 -HSL, C 10 -HSL, and 3-hydroxy-C 10 -HSL (34).…”
Section: Discussionmentioning
confidence: 99%
“…For human and plant pathogens, AHL-based communication systems allow a microbial community to strategically induce or repress expression of genes, specifically alleles encoding putative virulence factors, in response to environmental stimuli. Several reports have identified functional QS systems in various Burkholderia species and have shown that these bacterial communication networks both positively and negatively regulate numerous extracellular virulence factors in addition to contributing to animal pathogenicity (B. cepacia) (1,3,20,21,31,34,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations